Design and validation of the scale to evaluate interdisciplinary work in university students from Ecuador - Rodríguez-Torres, Ángel-Freddy; Cargua-García, Nancy-Isabel; Marín-Marín, José-Antonio; Moreno-Guerrero, Antonio-José; López-Belmonte, Jesús (IJERI: International Journal of Educational Research and Innovation, 2023)
Today students are faced with increasingly complex problems that require approaches that transcend disciplines, since they cannot be addressed in isolation. Interdisciplinarity is conceived as an act of exchange, of reciprocity between the disciplines and a possibility of enriching and integrating the elements of knowledge. The objective of this study is focused on designing, validating and making reliable an instrument that allows to assess the interdisciplinary competences of the students. An instrumental research design has been used in which 600 university students from Ecuador participated. In order to know the psychometric properties of the scale, different analyzes were carried out with the JASP statistical software. Various analyzes were performed, obtaining pertinent values. The correlations between the dimensions were positive in all cases and the factorial weights of each of them showed adequacy of each item with respect to the dimension of which it is a part. Finally, the reliability analysis of the instrument based on Cronbach's Alpha and McDonald's Omega coefficient yielded acceptable results, both for global reliability and for each of the dimensions that make up the instrument. It is concluded that the instrument designed is relevant to assess interdisciplinary skills in Ecuadorian students of higher education.